Przegląd doświadczeń europejskich i światowych w procesie pomiaru efektywności wykorzystania zasobów publicznego szkolnictwa wyższego - Ćwiąkała-Małys, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The findings from European and world’s studies in which the DEA method has been used indicate wide usage of the method. Additionally, we can see its research value in the area of higher education units in the world. Obviously, it is not recommended to draw unquestionable conclusions on the basis of the DEA method and its outcomes. However, what we can see from the studies, it contributes to a process of efficiency studies of higher education. Universities as units that operate on the basis of public resources should achieve their targets in the most effective way. Due to this fact, interest in the DEA method and attempts to extend research tools in Poland seems to be advisable. It is possible to base on broad world experience on the one hand, but on the other we can contribute to application of the method in higher education researches in Poland. In the future, what is indicated by many authors, it is desirable to study efficiency of an all-European or international model of higher education units.
Keywords: publiczne szkolnictwo wyższe; edukacja; finansowanie